Cluster Analysis of the Teacher – Applicants to be Enlisted in the Registry of Qualified Applicants for Public School Teachers: Basis for Policy Formu-lation - Apilada, Yolanda A.; Cameros, Christine G.; De la Rita, Mayalene S.; Ceniza, Maridel L.; Manlapas, Relly V. Manlapas; Golandrina, Jane (Future Science / FSH-PH Publications, 2023)
The Recruitment, Selection and Placement Core Group of the PRIME-HRM of the Department of Education Division of Butuan City conducted this research mainly to address the issues on the assessment of the Teacher applicants particularly in the scoring system which may eventually be hired in the Department of Education. To identify gaps in assessing teacher competencies, the researchers used the K-means cluster analysis to generate knowledge that could be the basis for policy formulation. An applicant can be in the Registry of Qualified Applicants if he/she passes the criteria in the selection relative to their qualifications and competencies. The researchers found two issues that need to be addressed. First, it is the experience and the English Proficiency Test (EPT) results. Experience is necessary because teaching is a skill which requires expertise, but we do not prioritize it over other criteria. Another gap is the English Proficiency Test result. English is an essential factor in the teaching profession since it is our second medium of speech and teachers are facilitators in the learning process of pupils and students. Thus, there is a need to revisit the EPT tool and propose modification if deemed necessary; English skills enhancement is duly recommended from Senior High School to Higher Education to develop mainly its basic communication proficiency; newly hired teachers will undergo training to enrich English aptitude; enhance the policy on recruitment process.